Zn/Fe bimetallic modified Spartina alterniflora-derived biochar heterostructure with superior catalytic performance for the degradation of malachite green - Hua Jing; Lili Ji; Zilong Li; Zhen Wang; Ran Li; Kaixuan Ju (Biochar, 2023)
Abstract In this study, the synchronous magnetized carbonization method was utilized for preparing photocatalysis ZnO-Fe@SC heterostructure, which exhibited degradation efficiency 99.14% (60 min) for malachite green (200 mg/L) and could still maintain good performance after 5 cycles. The prepared ZnO-Fe@SC was analyzed using UV–Vis DRS, PL, SEM, TEM, BET, FTIR, XPS and VSM, and LC–MS for degradation products. The results indicate that photocatalyst has favorable magnetic properties, chemical stability and low charge carriers (e−/h+) recombination rate. The modification of bimetals enables the composite photocatalyst to enhance the intensity of photogenerated electron transition. Moreover, quenching experiment revealed that the photo-generated holes (h+) and superoxide radicals (·O2−) were the dominant active species during the photocatalytic process, which degraded malachite green into small molecules by demethylation, deamination, ring-opening reactions as deducted from LC–MS analysis. ZnO-Fe@SC was prepared using a green, safe, low cost and operable synthetic method, which has a broad market potential in the field of environmental remediation. Graphical Abstract